Fine Particulate Concentrations in the Ambient Environment of a Major Haulage Vehicle Park - Fakinle, B.S.; Adeniran, J.A.; Okedere, O.B.; Jimoda, L.A.; Sonibare, J.A. (Ife Journal of Technology, 2015)
The study was carried out to determine the levels of particulates in the airshed of major vehicular park and suggest appropriate ways of controlling the ambient particulate concentrations. The ambient fine mode particulate number concentrations were measured at five different designated points in the park using the Met-One mode GT-321 particulate air monitor. Measurements were conducted both in the wet and dry seasons. The Results showed that the averaged 8 hr daytime particulate concentrations for 0.3, 0.5 and 1.0µm PM within the park were of the range 1.19 x 108 - 2.52 x 108 particles/m3 with an average of 2.25 x 108 particles/m3, 2.66 x 107 - 7.59 x 107 particles/m3 with an average of 5.08 x 107 particle/m3 and 3.17 x 106 - 9.82 x 106 particles/m3 with average of 6.97 x 106 particles/m3 respectively during the wet season and 1.22 x 108 - 1.73 x 108 particles/m3 with an average of 1.41 x 108 particles/m3, 1.58 x 107 - 3.99 x 107 particles/m3 with an average of 2.94 x 107 particles/m3 and 3.74 x 106 - 9.67 x 106 particles/m3 with an average of 6.48 x 106 particles/m3 respectively during the dry season. The Particulate Concentrations measured during the two seasons were within the maximum permitted limit of ISO Class 9 for PM1 required for a clean zone by International Standard Organization-ISO 146441. The study showed that vehicular activity could be one of the major contributors to ambient particulate concentration. Hence effective control measures such as cleaner technology, the use of catalytic converters, the use of alternative fuel and clean fuel and the implementation of emission standard should be employed in order to have an improved air quality based on ambient particulate concentration.